Priapismus - Hora, M; Ouda, Z (Casopis lekaru ceskych, 1999)
Priapism is prolonged, and usually painful, erection not associated with sexual desire. It is a relatively rare acute urological disease where treatment must be started within 6 hours after its development, as after a longer time interval due to ischaemia irreversible fibrotic changes of the cavernous tissue of the penis develop which lead to permanent erectile dysfunction. There may be either low flow priapism (inadequate outflow of blood from the cavernous tissue) or more rarely high flow priapism (excessive inflow of blood). Priapism is classified with regard to its aetiology into primary (cause unknown) or secondary. The causes of secondary priapism are most frequently overdosage of vasodilatating agents during intracavernous injection treatment of erectile dysfunction (specially papaverine), tumours (obstruction of the efferent veins or direct infiltration of the corpora cavernosa)--in particular carcinoma of the urinary bladder, prostate and rectum. Priapism is frequently due to injuries of the prostate and straddle injuries. 5% men with sickle-cell anaemia suffer from an attack of priapism. Treatment of priapism differs, depending on the type, and should be entrusted to an experienced urologist in an in-patient department.
Keywords: Priapism; Humans; mužské pohlaví; Male; lidé; priapismus